Loss of Wnt4 and Foxl2 leads to female-to-male sex reversal extending to germ cells - Ottolenghi, Chris; Pelosi, Emanuele; Tran, Joseph; Colombino, Maria; Douglass, Eric; Nedorezov, Timur; Cao, Antonio; Forabosco, Antonino; Schlessinger, David (Human molecular genetics, 2007)
The discovery that the SRY gene induces male sex in humans and other mammals led to speculation about a possible equivalent for female sex. However, only partial effects have been reported for candidate genes experimentally tested so far. Here we demonstrate that inactivation of two ovarian somatic factors, Wnt4 and Foxl2, produces testis differentiation in XX mice, resulting in the formation of testis tubules and spermatogonia. These genes are thus required to initiate or maintain all major aspects of female sex determination in mammals. The two genes are independently expressed and show complementary roles in ovary morphogenesis. In addition, forced expression of Foxl2 impairs testis tubule differentiation in XY transgenic mice, and germ cell-depleted XX mice lacking Foxl2 and harboring a Kit mutation undergo partial female-to-male sex reversal. The results are all consistent with an anti-testis role for Foxl2. The data suggest that the relative autonomy of the action of Foxl2, Wnt4 and additional ovarian factor(s) in the mouse should facilitate the dissection of their respective contributions to female sex determination.